1998
DOI: 10.1074/jbc.273.21.12732
|View full text |Cite
|
Sign up to set email alerts
|

Mapping Drug Interactions at the Covalent Topoisomerase II-DNA Complex by Bisantrene/Amsacrine Congeners

Abstract: To identify structural determinants for the sequencespecific recognition of covalent topoisomerase II-DNA complexes by anti-cancer drugs, we investigated a number of bisantrene congeners, including a 10-azabioisoster, bearing one or two 4,5-dihydro-1H-imidazol-2-yl hydrazone side chains at positions 1, 4, or 9 of the anthracene ring system. The studied bisantrene/amsacrine (m-AMSA) hybrid and bisantrene isomers were able to poison DNA topoisomerase II with an intermediate activity between those of bisantrene a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

1999
1999
2016
2016

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 23 publications
1
22
0
Order By: Relevance
“…4 and Table I), the human enzyme showed a clear preference for A ϩ1 (47 of 64 sites) and a complementary (although weaker) preference for T ϩ4 (28 of 64 sites), which conforms with earlier studies (29,33,34). The yeast protein also demonstrated a strong preference for A ϩ1 (29 of 61 sites) but an additional preference for T at position Ϫ1 (32 of 61 sites) as well as the complementary A at position ϩ5 (28 of 61 sites), which was not seen in the human enzyme.…”
Section: Different Base Preferences Of Amsacrine-and Mitoxantronestabsupporting
confidence: 91%
See 1 more Smart Citation
“…4 and Table I), the human enzyme showed a clear preference for A ϩ1 (47 of 64 sites) and a complementary (although weaker) preference for T ϩ4 (28 of 64 sites), which conforms with earlier studies (29,33,34). The yeast protein also demonstrated a strong preference for A ϩ1 (29 of 61 sites) but an additional preference for T at position Ϫ1 (32 of 61 sites) as well as the complementary A at position ϩ5 (28 of 61 sites), which was not seen in the human enzyme.…”
Section: Different Base Preferences Of Amsacrine-and Mitoxantronestabsupporting
confidence: 91%
“…The DNA sequence preference of drugs that target DNA top2 has been widely investigated (34). Early studies showed that topoisomerase-targeting drugs influence the sequence specificity of DNA cleavage by top2 compared with sites of DNA cleavage in the absence of drugs (28,29,39).…”
Section: Discussionmentioning
confidence: 99%
“…In general, drugs with similar shapes, and with shared pharmacophores and electronic structure, tend to have similar topoisomerase II-mediated DNA cleavage patterns, whereas topoisomerase II poisons of different chemical classes cause very different DNA cleavage patterns and/or cleavage intensity patterns (Capranico et al, 1993(Capranico et al, , 1994a(Capranico et al, , 1998Guano et al, 1999). However, there are exceptions to this rule.…”
Section: Discussionmentioning
confidence: 99%
“…18,19 Compounds were obtained by standard solution synthesis following the reported procedures, and the synthetic strategy is summarized in Scheme 1. Briefly, the procedure is based on a Friedel-Crafts acylation of the anthracene with acetyl chloride in the presence of AlCl 3 in dichloroethane.…”
Section: Synthesis Of Constrained Derivativesmentioning
confidence: 99%
“…We previously reported the synthetic procedure for compound Ant1,5. 18,19 Anthracene-1,5-diacetyl (2). A three-neck round bottom flask was charged with anthracene (10.00 g, 56 mmol) and AlCl 3 (23.00 g, 172 mmol) in 300.0 mL of dichloroethane.…”
Section: Synthetic Proceduresmentioning
confidence: 99%